Aksesibilitas Terhadap Informasi Keagamaan Bagi Penyandang Disabilitas Tuna Rungu: Visualisasi Tanda di Lingkungan Pusdai Jawa Barat - Junaenah, Inna; Hermawan, Hendy; Samodro, Samodro; Rigmalia, Dante (Jurnal HAM, 2023)
Human rights law encourages the implementation of state obligations by enacting policies that remove accessibility barriers for persons with disabilities, including a guaranteed access to information. Unfortunately, attention and efforts to facilitate the accessibility of people with deaf disabilities are insufficient, especially regarding religious information. The West Java Islamic Da’wah Center (Pusat Dakwah Islam/Pusdai), as one of the social service units within the local government, barely has a systematic policy basis to facilitate access to religious information, particularly for the “Friday Sermon” for persons with Hard of Hearing (HOH). This article identifies that human rights law can be the underlying basis for the fulfilment of visual communication for persons with HOH. This article discusses a visual design construction that may facilitate communication barriers for deaf-disabled persons in accessing religious information in Pusdai. By employing a socio-legal approach, including visual communication design lens, this study finds a gap in the visual information availability and facility for people with HOH. This study contends that visualization, in the form of moving and static signs, is necessary to facilitate the convenience of persons with HOH and it is seen as an effort to realize inclusive religious services. Such a measure needs to be incorporated into the National Action Plan on Human Rights (RANHAM) in West Java Province.